Effectiveness of the Management Indicators in Raising Revenue Municipalities of Lima Metropolitana 2013-2015 - Valencia Pomareda, Pedro Jaime (2017)
According to Articles 97 and 98 of the Organic Law of Municipalities N° 27972, coordination between local governments is established, establishing a pilot plan that features a Dashboard-BSC, whose indicators are shared by local governments Lima, with not very satisfactory results. In order to overcome this difficulty has undertaken a pilot strategic management plan, with the Balanced Scorecard-BSC, which interconnects prospects, indicators, targets and initiatives. Having reviewed this board follows that probably, among other variables, the weakness is in the management indicators, so far not achieved the desired objectives.